Characteristics of the 3 most common types of occupational accident in the spanish underground and surface mining, period 2003-2008 (2012)
The rate for work related accidents in the Spanish mining has decreased during recent years. However, the incidence rate per 100,000 workers in the Spanish mining sector in 2007 was significantly higher than the ones reported in the mining industry of other countries. This result implies that studies and research should be made in order to reveal the nature of the factors influencing the high incidence rates of the Spanish mining sector. Thus, this article offers features of the 3 most common types of accident of the Spanish mining industry during period 2003-2008. For each type of accident, the analysis proceeds as follows: 1) Modeling of the adjusted exponential distribution in terms of lost work days; 2) Calculation of the risk index adjusted by age group of injured workers; Identification of the 3 main deviations or immediate causes.